Experimental Investigation of Thermal Properties of Ternary Nanofluids in Water-Ethylene Glycol (60:40) Mixture - Anwar Ilmar Ramadhan; Wan Hamzah Azmi; Korada Viswanatha Sharma; Efrizon Umar (Journal of Applied Sciences and Advanced Technology, 2022)
In recent years, research is directed towards enhancing the thermo-physical properties of single-component nanofluids. Hence, a hybrid or composite nanofluid is developed to improve heat transfer performance. The thermophysical properties of the Al2O3-TiO2-SiO2 nanoparticles suspended in the base of water (W) and ethylene glycol (EG) blends with vol 60:40 or Ternary Nanofluids for various volume concentrations are investigated. The experiments were undertaken for the concentration volume of 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0% of Al2O3-TiO2-SiO2 nanofluids with 30, 40, 50, 60 and 70 °C. Thermal conductivity measurements and dynamic viscosity are carried out at temperatures ranging from 30-70 °C.  The highest thermal conductivity of Ternary nanofluids was obtained at a concentration of 3.0%, and the maximum increase was up to 27.1% higher than the base fluid (EG/W). Ternary nanofluids at a concentration of 0.5% give the lowest effective thermal conductivity of 14.4% at 70°C. Meanwhile, the evidence from the dynamic viscosity of the Ternary nanofluids is influenced by concentration and temperature. Furthermore, Ternary nanofluids behaviour as Newtonian fluid in volume concentration from 0.5-3.0%. The development of a new correlation for thermal conductivity and dynamic viscosity of Ternary nanofluids are precise. In conclusion, the combination of enhancement in thermal conductivity and a dynamic viscosity at a concentration of 3.0% has optimum conditions, which have more advantages for heat transfer than at other concentrations.